Guessing the game: An individual's awareness and assessment of a game's existence - Katarina Kostelic (Games, 2020)
In everyday life, games begin inconspicuously, leaving an individual to stumble upon their assessment of a situation. An unaware individual is unlikely to exhibit strategic behavior in a given situation, which highlights the importance of awareness examination. The purpose of this exploratory analysis is to examine awareness and assessment of a game's existence at the individual level. That requires examination of respondents' detection (as an indication of their awareness) and identification (as an indication of their assessment) of game elements in game-like situations and their relation to awareness of the game existence. The empirical data is collected using a scenario technique and is statistically analyzed. The results show that the respondents are, on average, at least partially aware of possibility for strategic interaction (even in vague situations). The revealed regularities point out to the relation of the game elements to game existence belief, but also indicate the presence of psychological biases and information utilization issues. For example, the respondents assign different levels of belief to game existence regarding possible losses or gains. Research limitations involve the use of a small convenience sample and lead to suggestions for results validation in future research. Possible implications of the results are discussed.
Keywords: 330; behavioral game theory; belief; game awareness; individual